Análise das implicações psicossociais do protagonismo para os jovens em situação de pobreza - Silva, Alexsandra Maria Sousa (2014)
This research is located in the meeting point between two fields of study and action: Psychology and Youth and it will approach leadership for young people in a poverty context. The relevance of this subject is shown through the emphasis with which the youth leadership concept is used in contemporary society, in a conceptual and practical dimension being a term full of facets and plurality. This way, the focus of the policies is to assume youth leadership in a way to implement this path as a way to overcome the situation of poverty. This reality is built in a way to impose young poor people with the need to be leaders. Consequently, it has the objective of analyzing the psycho-social implications of leadership in young poor people. Based on a qualitative methodology, the research was developed along with young people from a dance group, members of the Culture, Science, Art and Sport Urban Center (Centro Urbano de Cultura, Ciência, Arte e Esporte - CUCA) Che Guevara, a public policy for youth, located in Barra do Ceará, in the city of Fortaleza. The process of data gathering happened due to participating-observation, with the use of a Social-Economical Questionnaire with 11 young persons, with the facilitating of a focus group, with 7 young persons and 2 individual interviews with participants of the previous moments. The data was analyzed according to Bardin’s Content Analysis, with the help of qualitative analysis’ software Atlas TI 5.2. 37 categories have been obtained, and the ones related to the subject were selected and separated into large categories: “ways of life”, “leadership” and “public policies”. At the end of the study it can be noticed that psycho-social implications of leadership happen through fortification, leadership exercise and social acknowledgement. Fortification is related to autonomy and it is based on social support, with emphasis on family and institutional support. The leadership of young people takes as basis, dialog and co-participation. And social acknowledgement is related to the promotion of citizenship, which is related to participation and autonomy. It can be noticed that leadership makes itself present by a group of elements, which are of political, educational, social and psychological nature and being this way, can show a way of coping with a multidimensional poverty. The creation of spaces, in public policies, must happen in a way to enable the potentialities inherent to each young person, this way contributing to promote leadership based on a liberation praxis. Thanks to FUNCAP.